Assessment Methods of Usability and Cognitive Workload of Rehabilitative Exoskeletons: A Systematic Review - Laura Maria Alessandra La Bara; Luca Meloni; Davide Giusino; Luca Pietrantoni (Applied Sciences, 2021)
Robotic exoskeleton technologies are applied in the medical field to help patients with impaired mobility to recover their motor functions. Relevant literature shows that usability and cognitive workload may influence the patients’ likelihood to benefit from the use of rehabilitative exoskeletons. Following the PRISMA method, the present study aimed to systematically review the assessment methods of usability and cognitive workload in the use of exoskeletal devices for motor rehabilitation. The literature search was conducted in the Scopus and Web of Science bibliographical databases, using 16 keywords that were combined into one search query. A final sample of 23 articles was included in the review, from which 18 distinct assessment methods were identified. Of them, 15 aimed to assess usability, whereas 3 aimed to assess cognitive workload in the use of rehabilitative exoskeletons. Some of the identified methods (e.g., SUS, QUEST, SWAT, and NASA-TLX) showed good psychometric properties and were therefore proven to be appropriate to assess usability and cognitive workload while performing exoskeleton-based rehabilitation. The current study may contribute to the development of guidelines and analytical tools for exoskeletons’ usability and exoskeleton-related patients’ cognitive workload in the domain of medical rehabilitation.